2003
DOI: 10.1086/502121
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Percutaneous Injury Patterns in A Multi-Hospital System

Abstract: Objective:Determine differences in patterns of percutaneous injuries (PIs) in different types of hospitals.Design:Case series of injuries occurring from 1997 to 2001.Setting:Large midwestern healthcare system with a consolidated occupational health database from 9 hospitals, including rural and urban, community and teaching (1 pediatric, 1 adult) facilities, ranging from 113 to 1,400 beds.Participants:Healthcare workers injured between 1997 and 2001.Results:Annual injury rates for all hospitals decreased durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
(6 reference statements)
0
11
0
1
Order By: Relevance
“…[3][4][5][6] According to Jagger et al, 7 although sharps injuries in the nonsurgical setting have decreased substantially since the passage of the Needlestick Safety and Prevention Act of 2000, reported sharps injuries in the surgical setting have actually increased 6.5%. BBF exposures, therefore, remain a common health risk among healthcare workers, particularly for surgical staff members.…”
mentioning
confidence: 99%
“…[3][4][5][6] According to Jagger et al, 7 although sharps injuries in the nonsurgical setting have decreased substantially since the passage of the Needlestick Safety and Prevention Act of 2000, reported sharps injuries in the surgical setting have actually increased 6.5%. BBF exposures, therefore, remain a common health risk among healthcare workers, particularly for surgical staff members.…”
mentioning
confidence: 99%
“…35,[37][38][39] Although all health care staff who provide direct patient contact are at-risk for exposure to blood and body fluids, surgical and obstetrics staff are often cited as a particularly vulnerable occupational group. [40][41][42][43] NaSH data have shown that 28% of injuries were reported in operating theaters. 7 In other studies examining the risk of injury in operating theaters, 93% of injuries were sharps related, and in half of those injuries, suture needles were implicated.…”
Section: Risk Groups For Exposurementioning
confidence: 99%
“…Delici-kesici alet yaralanmaları ve kan veya vücut sıvılarının cilt veya mukozaya temas etmesi sağlık çalışanlarına çeşitli enfeksiyonların bulaşında rol oynamaktadır (1,2). Bulaşma esas olarak perkütan yol kimi zaman da mukozal yolla meydana gelmektedir.…”
Section: Introductionunclassified